Paparan Benzena terhadap Kesehatan Pekerja di Sektor Industri: Kajian Literatur - Josepin Karolina; Rifqa Masry; Windi Audina; Abdurrozzaq Hasibuan (Annusfy : Journal of Multidisciplinary Research, 2026)
Benzene exposure in industrial workplaces remains a major concern in occupational health due to its toxic and carcinogenic properties. This study aims to analyze the relationship between benzene exposure and health effects among workers in various industrial sectors. The method used was a literature review of peer-reviewed scientific articles published between 2021 and 2026 via the Google Scholar database. Articles meeting the inclusion criteria were then analyzed thematically to identify exposure levels, risk factors, and the resulting health impacts. The findings indicate that benzene exposure still occurs across various industrial sectors, with concentrations found both below and above established threshold levels. Even low-level exposure has the potential to cause observable biological effects, such as elevated biomarkers in workers. Risk levels are influenced by several factors, including exposure duration and intensity, tenure, and smoking habits. The resulting health impacts are multisystemic, including hematological disorders, impaired liver and kidney function, respiratory system disorders, and an increased risk of cancer. Additionally, variations in findings across studies indicate that workplace conditions, exposure measurement methods, and the effectiveness of control measures significantly influence the risk levels experienced by workers. In conclusion, benzene exposure remains a significant occupational health risk even at low concentrations. Therefore, more optimal and sustainable control efforts are needed, including routine monitoring, improvements in technical controls, and the consistent use of personal protective equipment to comprehensively protect workers’ health.